PENGARUH KUALITAS PELAYANAN KARTU KREDIT TERHADAP KEPUASAN KONSUMEN PADA BANK KB BUKOPIN REGIONAL BANDUNG - Andri Susan Kurnia; Dian Candra Fatihah (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This research purposed to know how the effect of the quality of credit card service on consumer satisfaction in Bank KB Bukopin Regional Bandung. The research method was used in this research was a verifiable descriptive method by collecting data from field studies, questionnaires and literate studies. The population in this research is a credit card consumer with 40 samples by using sample random sampling method. Primary data in this research are derived from a questionnaire that measures a Likert scale and was statistically treated with an SPSS version 26.0 program, while the data analysis techniques were used simple linear regression and intervariabel correlation techniques. From the research that had been done, there was concluded that the quality of the service has a solid relation with consumer satisfaction. This is known from a coefficient value of credit card services to consumer satisfaction at 0.863 at high relations rates interval. The result of the t hypothesis test stated that there was an effect between the quality of credit card service to consumer satisfaction in Bank KB Bukopin Regional Bandung because it had a higher value t than t table (10.54 > 1.68595). The problem encountered is the high level of consumer complaints about the slow input of data on the system at the Bukopin Bank for every credit card payment